Efficacy and safety of a herbo-mineral ayurvedic formulation ′Afrodet Plus®′ in male rats - Dhumal, Rohit; Vijaykumar, Tushara; Dighe, Vikas; Selkar, Nilakash; Chawda, Mukesh; Vahlia, Mahesh; Vanage, Geeta (Journal of ayurveda and integrative medicine, 2013)
Background: Reverse pharmacology for drug development has been highly productive and cost-effective in recent past as it is based on the documented therapeutic effects of plants in ancient texts. Afrodet Plus® is formulated for the treatment of male infertility, which contains ancient herbo-minerals. Its efficacy and safety are validated through this animal study in reverse pharmacology mode. Objectives: This study was undertaken to evaluate efficacy and safety of an Ayurvedic formulation Afrodet Plus® in adult male rats. Materials and Methods: Twelve male rats (Holtzman) between 8 and 10 weeks of age were randomly selected and animals were assigned to a control and two treatment groups. Dosing was performed daily. Various parameters such as weekly body weight, hematology, serum testosterone levels, epididymal sperm count, and efficiency of Daily Sperm Production (DSP) were evaluated. Results: It was found that epididymal sperm count had significantly increased in both low-dose (+27.39%) and high-dose (+40.5%) groups as compared to control group. The DSP also showed an increase of 43.7% at high dose of 180 mg/kg body weight as compared to the control group. An increase in sperm motility and especially progressive motility was observed when evaluated by Computer Assisted Semen Analyzer. Histological evaluation of testicular tissue for spermatogenic index revealed that the index had increased in treatment group as compared to control group. Conclusion: This study revealed that oral administration of Afrodet Plus® resulted in significant increase in DSP in the testis along with increase in epididymal sperm count and progressive motility as compared to control group without producing any treatment-related adverse effects. These findings provide the documentary evidence that the use of Afrodet Plus® at 90 and 180 mg/kg body weight is effective and safe for the treatment of male infertility especially to improve sperm count and progressive motility.